Targeting alveolar epithelial cell metabolism in pulmonary fibrosis: Pioneering an emerging therapeutic strategy - Tengkun Dai; Tengkun Dai; Yidan Liang; Yidan Liang; Xin Li; Xin Li; Jiamin Zhao; Jiamin Zhao; Guangqin Li; Qihong Li; Lin Xu; Lin Xu; et al. (Frontiers in Cell and Developmental Biology)
Pulmonary fibrosis (PF) is a chronic and progressive lung disease, characterized by excessive deposition of fibrotic connective tissue within the lungs. Advances in transcriptomics, proteomics, and metabolomics have enhanced our understanding of PF’s pathogenesis. Recent studies have indicates that metabolic abnormalities in alveolar epithelial cells (AECs) play a central role in the pathogenesis of PF. Metabolic reprogramming of AECs affects cellular senescence, endoplasmic reticulum stress, and oxidative stress in AECs, while also promoting fibrotic progression through various signaling pathways. This review focuses on therapeutic strategies targeting the metabolism of AECs. It comprehensively explores the role of metabolic pathways through glucose metabolism, lipid metabolism, and amino acid metabolism in the pathogenesis of PF, aiming to provide novel theoretical support and research perspectives for preventing and treating pulmonary fibrosis.